Lithium Sulfide–Carbon Composites via Aerosol Spray Pyrolysis as Cathode Materials for Lithium–Sulfur Batteries - Hart, Noam; Shi, Jiayan; Zhang, Jian; Fu, Chengyin; Guo, Juchen (Frontiers in Chemistry, 2018)
We demonstrate a new synthetic technique to produce lithium sulfide-carbon composite (Li2S-C) cathodes for lithium-sulfur batteries via aerosol spray pyrolysis (ASP) followed by sulfurization. Specifically, lithium carbonate-carbon (Li2CO3-C) composite nanoparticles are first synthesized via ASP from aqueous solutions of sucrose and lithium salts including nitrate (LiNO3), acetate (CH3COOLi) and Li2CO3, respectively. The obtained Li2CO3-C composites are consequentially converted to Li2S-C through sulfurization by reaction to H2S. Electrochemical characterizations show excellent overall capacity and cycle stability of the Li2S-C composites with relatively high areal loading of Li2S and low electrolyte/Li2S ratio. The Li2S-C nanocomposites also demonstrate clear structure-property relationships.